2021
DOI: 10.1177/12034754211024124
|View full text |Cite
|
Sign up to set email alerts
|

Electrodessication Matricectomy With Modified Hyfrecator Tip: Case Series and Literature Review

Abstract: Nail matricectomy is indicated in the management of painful onychodystrophies, including recalcitrant onychocryptosis, onychogryphosis, onychauxis, and refractory onychomycosis. Although many matricectomy methods have been described, with phenolization being the best studied, no one method has clearly emerged as superior. We present a series of 14 patients who underwent a total of 18 matricectomies with either phenolization or electrodessication (ED) in a private dermatology office, and describe a simple and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Some literatures reported that there is no significant difference between the results of matricectomy with electrocautery, phenol, and cryotherapy in the esthetical term. The ingrown toenail patients treated with these procedures had an adequately high satisfaction level in the aesthetical term with the minimal postsurgical wound [17][18][19]. In this report, patients did not complain related to any aesthetic disturbance either related to the big toe nail growth or shape after surgery.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Some literatures reported that there is no significant difference between the results of matricectomy with electrocautery, phenol, and cryotherapy in the esthetical term. The ingrown toenail patients treated with these procedures had an adequately high satisfaction level in the aesthetical term with the minimal postsurgical wound [17][18][19]. In this report, patients did not complain related to any aesthetic disturbance either related to the big toe nail growth or shape after surgery.…”
Section: Discussionmentioning
confidence: 80%
“…Electrosurgery was one of the methods to treat ingrown nail that used high energy, while electrocautery only used a small electrical current utilizing the metal wires applied to the target tissue to burn or coagulate a specific tissue area and was then damaged. Electrocautery is a relatively safe procedure since the electrical energy does not flow through the patient's body, yet only affects the target tissue [17,18]. In this case series, electrocautery has been performed and chosen rather than electrodessication or electrofulguration because electrocautery is more appropriate for nonconductive tissues like nail, bone, and cartilage.…”
Section: Discussionmentioning
confidence: 99%